Comparing stress responses of F1 and domesticated striped bass (Morone saxatilis) following a repeated acute stressor. (11th May 2021) - Kenter, Linas W.; Breton, Timothy S.; Berlinsky, David L.
Abstract: Recent growth in striped bass aquaculture has generated interest in broodstock development programs for improved growth, disease resistance and stress tolerance. This research evaluated differential stress responsiveness of captive‐bred striped bass originating from Canada, Virginia, Florida and a domestic strain, following a repeated acute stressor. Fish were communally stocked into a six tank recirculating system, and fish in three tanks were net‐chased for 1 min two days/week (stressed), and three undisturbed tanks served as controls. After 14 weeks, fish in the control and stressed treatments were chased, and blood collected from all fish in one tank per treatment at 0, 1 and 3 h post‐stressor. Growth, cortisol, glucose, haematological indices and selected hepatic gene expression were compared among strains and between treatment groups. To further compare cortisol responsiveness, a second study was conducted with lower net chasing frequency (once/month) and cortisol measured. A cortisol stress response was not detected in Canada fish in either study, but all other strains exhibited similar expression patterns. Differences in plasma parameters, growth and immunocompetence were detected, but no single measure predicted greater growth. These results indicate that strains differ in acute stress responsiveness, which may be useful in selective breeding programs.